Exploring Management Options for Expedition Cruise Tourism in the Canadian Arctic - Orawiec, Andrew Karl (Université d'Ottawa / University of Ottawa, 2025)
Expedition cruise tourism in the Canadian Arctic presents unique management challenges due to its operational characteristics and the region's jurisdictional complexity. Unlike other forms of marine vessel traffic that follow more predictable routes, expedition cruise vessels frequently deviate from common shipping corridors to enhance visitor experiences, including scenic cruising in fjords and conducting shore landings at culturally and ecologically sensitive sites. This operational model creates potential conflicts with Inuit use of both marine and terrestrial areas, effectively competing for some of the same resources and raising concerns about potential impacts on the environment, wildlife, and cultural sites. This dissertation examines expedition cruise tourism management in the Canadian Arctic, with particular emphasis on the territory of Nunavut, Canada, to achieve the overarching aim of better understanding current management approaches to identify opportunities for improvement. This research addresses several existing important knowledge gaps including: 1) an absence of a publicly available comprehensive analysis of the regulatory and management frameworks applicable to expedition cruise tourism in Nunavut; 2) a limited understanding of the potential implications to expedition cruise operations stemming from proposed changes in existing management tools associated with existing and emerging marine protected area designations; 3) an absence of baseline data on visitor activity at remote shore locations in the region; and 4) limited information on the application of site-specific terrestrial management approaches that may constitute best practices in the Arctic. These gaps were addressed through three key research objectives within this dissertation, including to: 1) produce a conceptual overview of the management and regulatory frameworks for marine tourism within Nunavut waters, including an assessment of the relative effectiveness of these identified tools and frameworks in addressing Inuit concerns; 2) explore the impact of the establishment of Tallurutiup Imanga National Marine Conservation Area (TINMCA) and the potential contributions towards improving the management of expedition cruise tourism within its boundaries; and 3) examine cruise passenger activity at remote shore locations, forming a baseline understanding of visitor use at these sites and examining the need for appropriate management strategies. To achieve these objectives, several methods were employed including policy, content, and gap analyses, as well as a variety of Geographic Information System (GIS) analyses (i.e. mapping of vessel movements, visualizations of historical shore visit locations, and overlaying of shapefiles representing the proposed TINMCA zoning framework), as well as spatiotemporal analysis of GPS tracking data from cruise passengers in the field. Key results of this dissertation research reveal that while current regulatory frameworks effectively address vessel safety and environmental protection, they remain limited in their ability to address specific Inuit concerns. However, it was found that emerging approaches show promise in filling these gaps, such as new marine conservation mechanisms, a reconceptualization of the role of shore-based permitting regimes, and voluntary measures. The analysis of TINMCA's zoning framework probed the potential application of these emerging approaches, further identifying both opportunities and challenges in aligning marine spatial planning with existing terrestrial permitting systems. Finally, the examination of visitor movement patterns at remote shore locations revealed the need for improved terrestrial management strategies to protect sensitive cultural and environmental features. This research contributes to both academic literature and practical management applications by providing a foundation for developing more effective, culturally appropriate approaches for expedition cruise tourism in the Canadian Arctic. The findings can be utilized by federal and territorial authorities, Inuit organizations, and industry stakeholders to ensure self-determined and sustainable tourism development that respects both broader conservation objectives for a globally significant region and Inuit rights.
Keywords: Marine Tourism; Canadian Arctic; Nunavut; Marine Governance; Site-Specific Management; Marine Protected Areas; Ocean Policy